Long-Chain Polyunsaturated Fatty Acid Concentrations in Breast Milk from Chinese Mothers: Comparison with Other Regions - Li, Shi-Ying; Dong, Xiao-Li; Wong, Wing-Si Vincy; Su, Yi-Xiang; Wong, Man-Sau (International Journal of Child Health and Nutrition, 2015)
Long-chain polyunsaturated fatty acids (LC-PUFA), especially linoleic acid (LA), arachidonic acid (AA), alpha- linolenic acid (ALA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are essential to infant growth and development during early life. Up till now, there is only limited number of studies with large sample size on LC-PUFA in breast milk in China. In order to better understand the LC-PUFA levels in Chinese women, we report an analysis that included 44 studies of 3815 subjects from the latest 10-year peer-reviewed papers of breast milk studies of fatty acid profiles from China and other regions: Asia (excluding China), Europe, America and Africa. The results showed that Chinese women had significantly higher LA and ALA levels in the breast milk than European and other Asian women. The DHA level in the breast milk of Chinese women meets the Chinese and international recommended intake for young infants. This review provides comprehensive investigation on the LC-PUFA levels in the mature milk of Chinese women in most recent publications and server as a reference for further studies on human milk in China.